Classification of soil infiltration rate depending on the Hydrological soil group map South East Iraq - J. Al Marsumi, Khalid; M. Al Shamma, Aysar (Iraqi Journal of Science, 2021)
The study area is located in the East of Missan governorate, southeast of Iraq between (32°'29.52" – 32°37'30") latitude and (46°46'21.16" – 47°58'53.52")longitude. It encompasses an area of (1858 ) with elevation ranges from 8 to 165m. Soil is a natural body that exists as part of the pedosphere and which performs four important functions. It is a medium for plant growth and a means of water storage, supply and purification. The spatial mapping of soil usually involves delineating soil types that have identifiable characteristics. The delineation is based on many factors such as geomorphologic origin and conditions under which the soil is formed. Hydrologic soil group (HSG) refers to the classification of soils based on their runoff , producing characteristics and their infiltration rate. Soils are assigned to 4 hydrologic groups namely Group A - high infiltration rate when wet, low runoff potential, Group B - moderate infiltration, low runoff potential, Group C - slow infiltration, higher runoff potential, and Group D - very slow infiltration rate, highest runoff potential. According to the USDA soil classification system, four hydrological soil groups are recognized: A, B, C, and D with 19%, 48%, 32%, and 1%, respectively, the high percentage extension of moderately infiltration group (B and C).